2018
DOI: 10.1021/acsami.8b03702
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum and Niobium Codoped B-Site-Ordered Double Perovskite Catalyst for Efficient Oxygen Evolution Reaction

Abstract: An abundant, highly active, and durable oxygen evolution reaction (OER) electrocatalyst is an enabling component for a more sustainable energy future. We report, herein, a molybdenum and niobium codoped B-site-ordered double perovskite oxide with a compositional formula of BaCoMoNbO (BCMN) as an active and robust catalyst for OER in an alkaline electrolyte. BCMN displayed a low overpotential of 445 mA at a current density of 10 mA cm. BCMN also showed long-term stability in an alkaline medium. This work hints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 24 publications
(35 reference statements)
1
37
0
1
Order By: Relevance
“…It is critical to tune the electronic structure of the B site for the electrochemical behavior of perovskite oxides; hence, doping the B-site is the most facile way in governing the OER performance. 49,56 For instance, Shao group demonstrated that B-site doping of SrTiO 3 with cobalt and iron elements resulted in an improved electrocatalyst for OER. 60 (e) schematic illustration of the main origin of the OER activation for SCP sample during ADT.…”
Section: B-site Dopingmentioning
confidence: 99%
“…It is critical to tune the electronic structure of the B site for the electrochemical behavior of perovskite oxides; hence, doping the B-site is the most facile way in governing the OER performance. 49,56 For instance, Shao group demonstrated that B-site doping of SrTiO 3 with cobalt and iron elements resulted in an improved electrocatalyst for OER. 60 (e) schematic illustration of the main origin of the OER activation for SCP sample during ADT.…”
Section: B-site Dopingmentioning
confidence: 99%
“…[65] They found that Mo and Nb co-doped double perovskite (Ba 2 CoMo 0.5 Nb 0.5 O 6−δ ) exhibited the enhanced intrinsic OER activity with a low Tafel slop (77 mV dec −1 ) and a low overpotential (435 mV) to reach 10 mA cm −2 . [66] Recently, Xu et al introduced redox inactive Zr and Y ions to prepare the modified perovskite oxides (BaCo 0.5−x Fe 0.5−x Zr x Y x O 3−δ , BCF(ZY) x ). The overpotential at 10 mA cm −2 of BCF(ZY) 0.1 was merely 320 mV in alkaline condition, and the intrinsic activity of such catalyst was about 52 times higher than the benchmark catalyst IrO 2 , due to the fast charge transfer and facile adsorption of OH − and desorption of O 2 .…”
Section: B-site Substitutionmentioning
confidence: 99%
“…In contrast, LSC required an overpotential of 420 mV to reach 10 mA cm −2 with a Tafel slope of 131 mV dec −1 and K-MoSe 2 exhibited negligible OER activity. It has been reported that the OER performance of perovskite oxide can be improved by the doping effect of molybdenum 30 . We thus conducted XPS analysis of Mo and Se in LSC/K-MoSe 2 under OER condition after water electrolysis to elucidate the potential doping effect of Mo on the OER performance of LSC/K-MoSe 2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%